Wittgenstein snd Psychoanalysis: Approaches from language, ethics and the subject (ALPHA. Journal of Arts, Literature and Philosophy, 2022)
The article seeks to inquire about the link between Wittgenstein's elaborations and psychoanalysis. Reasoning stops at Wittgenstein's proposals on the self-referential impossibility of language, ethical acts and psychoanalysis. In this context, he sketches a possible response to the criticisms that Wittgenstein directed to psychoanalysis, pondering them from three central notions in Jacques Lacan's work: causality, fiction and the idea of subject.  In a second time, the article proposes to think about the link between ethics and subjectivity, from the temporality which introduces, in the human perspective, the dynamic drive.
Keywords: Wittgenstein; Psychoanalysis; Ethics; time; subjectivity